"I Want to Make it Right": A 46 Year-old Woman with End Stage Renal Disease and Her Australian Aboriginal Partner Make Significant Choices. (2nd October 2017) - Glenister, David
Abstract : Our case study subject, "Ruby", is a 46 year-old female suffering from a chronic renal condition, admitted to Royal Melbourne Hospital. As she, along with partner Charlie and daughter Amanda, received care from several members of Pastoral and Spiritual Care Services, as well as the Aboriginal Liaison Officer, we have decided to present a co-written case study, with each participant writing their own view in their own voice. Ruby's care included all the interventions recognized by Spiritual Health Victoria: spiritual assessment, spiritual support, spiritual counselling or guidance and spiritual ritual. 2 This latter intervention became very significant as Ruby declined, receiving palliative care, and included both religious ritual and legacy creation. On paper – or the hospital electronic database – Ruby's admission looks like failure, but as this case study reveals, within her physical decline and treatment, there was significant emotional and spiritual healing, leading to a relatively "good death".